Parent descriptions of the presentation and management of anxiousness in children on the autism spectrum. (May 2019) - Adams, Dawn; Young, Kate; Simpson, Kate; Keen, Deb
The complex interaction between anxiety and autism has led to debate about the presentation of anxiety in individuals on the spectrum and questions about the extent to which traditional checklists assess the entire range of symptomatology. Moreover, studies to date have not explored how the presentation of anxiety may differ between settings. Through a combination of open-ended questions, closed questions and standardised measures, parents of 173 children (aged 6–13) on the autism spectrum provided (1) descriptors of their child's anxiety at home, school and in the community and (2) strategies used to reduce their child's anxiety in each setting. Over half (52.6%) felt their child was anxious at home, 77.6% at school and 76.2% in the community. Parents reported differing presentations of anxiety between settings, with the majority of descriptions relating to observable, behavioural changes (e.g. hides/shuts down, repetitive behaviours) rather than cognitive or physiological signs. Parents also reported using different strategies across settings. The use of open-ended questions allowed the identification of signs of anxiety not explored within traditional questionnaires and highlighted the potential for signs to vary across settings. This knowledge is critical to inform the development or adaptations of anxiety measures and interventions.